In Crohn's Disease, Anti-TNF-α Treatment Changes the Balance between Mucosal IL-17, FOXP3, and CD4 Cells. (14th June 2012) - Hölttä, Veera; Sipponen, Taina; Westerholm-Ormio, Mia; Salo, Harri M.; Kolho, Kaija-Leena; Färkkilä, Martti; Savilahti, Erkki; Vaarala, Outi; Klemetti, Paula
Abstract : Aim . In Crohn's disease (CD), anti-TNF-α treatment is a potent medication. We aimed to characterize the effect of anti-TNF-α treatment on T effector and regulatory cells. Material and Methods . We studied T-effector and regulatory cells on cellular and mRNA levels in intestinal biopsy samples from 13 Crohn's disease patient. Biopsies were obtained at baseline and 3 months after anti-TNF-α treatment, and from 14 inflammation-free control subjects. Results . Patients had higher numbers of ileal IL-17 + and forkhead box P3 (FOXP3) + cells than did control subjects, both before ( P ≤ 0.001 and P ≤ 0.05, resp.) and after the anti-TNF-α treatment (P ≤ 0.01, P ≤ 0.01 ). Intestinal interferon-γ and IL-17 mRNA expression was higher in Crohn's disease and remained elevated after anti-TNF-α treatment. The ratio of IL-17 + cells to CD4 + cells decreased (P ≤ 0.05 ) and compared to baseline the ratio of IL-17 + cells to FOXP3 + was lower after treatment (P ≤ 0.05 ). Conclusions . TNF-α-blocking agents improved intestinal balance between IL-17 + T-effector and regulatory T cells, although intestinal IL-17 upregulation remained elevated.